The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acsami.5b06068
|View full text |Cite
|
Sign up to set email alerts
|

Highly Improved Efficiency of Deep-Blue Fluorescent Polymer Light-Emitting Device Based on a Novel Hole Interface Modifier with 1,3,5-Triazine Core

Abstract: We present an investigation of deep-blue fluorescent polymer light-emitting diodes (PLEDs) with a novel functional 1,3,5-triazine core material (HQTZ) sandwiched between poly(3,4-ethylene dioxythiophene):poly(styrene sulfonic acid) layer and poly(vinylcarbazole) layer as a hole injection layer (HIL) without interface intermixing. Ultraviolet photoemission spectroscopy and Kelvin probe measurements were carried out to determine the change of anode work function influenced by the HQTZ modifier. The thin HQTZ lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Subsequently, the product of the reaction was purified by dialysis to remove catalyst Tris, free DA monomerm and DA-based oligomer with low molecule weight. It is interesting that DA:PSS showed a relatively lower acidity with a pH of 5.3, compared with the pH of 1.9 for PEDOT:PSS . Considering the deep brown color freeze-dried product, we proposed that DA was oxidized into new compounds.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Subsequently, the product of the reaction was purified by dialysis to remove catalyst Tris, free DA monomerm and DA-based oligomer with low molecule weight. It is interesting that DA:PSS showed a relatively lower acidity with a pH of 5.3, compared with the pH of 1.9 for PEDOT:PSS . Considering the deep brown color freeze-dried product, we proposed that DA was oxidized into new compounds.…”
Section: Resultsmentioning
confidence: 91%
“…Poly­(3,4-theylene dioxythiophene):poly­(styrene sulfonic acid) (PEDOT:PSS) is one of the most successful and excellent water-soluble p -type materials as it has advantages including tunable high conductivity, high transparency in UV–visible region, the capability of smoothing the ITO morphology and so on. There are still some drawbacks including poor device lifetime induced by its acidity, structural and electronic inhomogeneity. Considering the weakness of PEDOT:PSS, many alternatives of PEDOT have been widely explored in previous work. Some work related to hydroquinone–quinone complexes on molecular electronics has been reported. , Motivated by our curiosity on the potential of electron-rich aromatic phenolic compounds to act as hole-transport materials, recently we further applied phenol-based material such as lignin-based derivatives as p -type transport materials in OPVs and OLEDs for the first time. In general, aromatic phenolic derivatives (PDs) are well-known as unstable compounds as they can be readily converted into fragile phenolic radicals (PRs); thereby, studies of their potential as p -type material are rarely reported. In fact, PDs and PRs are not as vulnerable as we postulate based on a traditional viewpoint.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymeric fluorescent dye (PFD) are the functional polymers which have a chromophoric center within their structure [29][30][31][32][33] . Owing to the inherent non-leaching behavior and good light fastness combined with the special properties of polymers, polymer bonded dyes or reactive dyes maybe play more important roles [34][35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%